RELASI ANTARA TOLERANSI UMAT BERAGAMA DENGAN KEHIDUPAN BERMASYARAKAT PERSPEKTIF ISLAM (Al-Qur’an dan Hadits - Raihan Diva Amrulloh (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
Indonesia is a heterogeneous country, where there is a lot of diversity in various aspects in it. This has an impact on the social conditions that occur in Indonesian society, both positive and negative impacts. One of them is the element of tolerance between religious groups that must exist in the strata of society, which sometimes becomes the cause of problems. The purpose of this paper is to discuss how the level of tolerance experienced by the Indonesian people, which can then be understood as the dynamics of life in a country full of diversity. This paper uses the library research method where sources are obtained from several types of sources, including: the Qur'an, Hadith, accredited books and scientific journals. Finally, the result of this paper is to tell full and sincere tolerance regardless of any background, which of course is based on the Qur'an and Hadith, so as to produce a condition of society full of peace, and with such tolerance the quality index of the nation can increase and other things can be further developed.